A MANAGEMENT SYSTEM FOR PREVENTING INTENTIONAL FOOD CONTAMINATION BASED ON RISK ANALYSIS - Navarrete, Ramón; Lario Esteban, Francisco Cruz (Brazilian Journal of Operations & Production Management, 2016)
In today’s globalized world the number of risks in supply chains are increasing and the threats are becoming more complex. All the risks and threats can have a severely negative impact on markets. Some of these threats are terrorism, piracy and theft. Within the food industry, Food Terrorism has gained relevance due to the extreme consequences it may have on both public health and the market. Food Terrorism refers to the intentional contamination of food in any link of the supply chain, which covers everything from production to consumption. The Food Defense refers to the analysis, control and improvement of prevention mechanisms of those attacks; that is, the Food Defense involves a Risks Management. In general terms, this paper focuses on a proposal formulation based on a risk analysis that allows establishing a management system for preventing intentional food contamination and the improvement of the security of the supply chain. Given the recent events in Paris, on November 13, 2015, consideration has also been given to the present situation and the importance of the issue of preventing terrorism. This initial study covers only the theoretical methodological proposal and focusses only on the companies of the alimentary sector of Guanajuato State in Mexico. However, it may extend into a research plan security of food supply chain.